2021
DOI: 10.3390/geosciences11060243
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness and Strength of Stabilized Organic Soils—Part I/II: Experimental Database and Statistical Description for Machine Learning Modelling

Abstract: This paper presents the experimental database and corresponding statistical analysis (Part I), which serves as a basis to perform the corresponding parametric analysis and machine learning modelling (Part II) of a comprehensive study on organic soil strength and stiffness, stabilized via the wet soil mixing method. The experimental database includes unconfined compression tests performed under laboratory-controlled conditions to investigate the impact of soil type, the soil’s organic content, the soil’s initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Here, biochar was observed to be far more effective compared to the IBPs, with a strength increase of up to 80% for BC4. These results are similar to previous findings on peat stabilisation [27,31,95]. The stabilisation effect can possibly be attributed to the water retention (high absorption capacity) of the biochar and densification [32,96].…”
Section: The Stabilisation Effect For Different Binders In Peatsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, biochar was observed to be far more effective compared to the IBPs, with a strength increase of up to 80% for BC4. These results are similar to previous findings on peat stabilisation [27,31,95]. The stabilisation effect can possibly be attributed to the water retention (high absorption capacity) of the biochar and densification [32,96].…”
Section: The Stabilisation Effect For Different Binders In Peatsupporting
confidence: 91%
“…Previous research has also shown that a lower liquidity index could imply a higher strength [98], but the opposite effect was observed herein as the liquidity indices were approximately 0.9-1.0 and 1.5-2.0 for the Onsøy and Tiller-Flotten clays, respectively. [27,31,95]. The stabilisation effect can possibly be attributed to the water r absorption capacity) of the biochar and densification [32,96].…”
Section: The Strength Difference Between the Onsøy And Tiller-flotten...mentioning
confidence: 99%